2009
DOI: 10.2478/v10109-010-0038-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of high tone power therapy on the peripheral microcirculation in the lower limbs

Abstract: Microcirculation is an element of the circulatory system between the arterial and vascular system. It consists of, among proper capillary vessels, arterioles, venules, lympha- Wpływ terapii energotonowej na mikrokrążenie obwodowe kończyn dolnychThe infl uence of high tone power therapy on the peripheral microcirculation in the lower limbs numer DOI 10.2478/v10109-010-0038-3 Streszczenie:Jedną z najnowszych metod wspomagania leczenia wielu schorzeń jest terapia energotonowa. Jest ona nowoczesnym sposobem terap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 5 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…Nowakowska et al in their study observed increased blood ow in the microcirculation of the lower limbs after applying the HiToP [10]. It is possible that in the case of patients after ACL reconstruction in whom the HiToP was used a similar phenomenon occurred, which resulted in reduction of swelling and the lack of effusion after applied therapy.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Nowakowska et al in their study observed increased blood ow in the microcirculation of the lower limbs after applying the HiToP [10]. It is possible that in the case of patients after ACL reconstruction in whom the HiToP was used a similar phenomenon occurred, which resulted in reduction of swelling and the lack of effusion after applied therapy.…”
Section: Discussionmentioning
confidence: 92%
“…It directly affects cell metabolism, improving metabolic processes in tissues, and pain relief. It can also be used to obtain stimulating effects of the current, in this case also for electro stimulation of the quadriceps [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations